(3cJGH aj EUdGM GdCOhjI GdeSgdIs - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s
(3ChdgG (B:s
(3ef Pdc EUdGM GdSbeb EPG cSQJg Ch aQcJg CSQY GdfjQGf s
(3BNQgG (B:s
(3hCeG GdCSHGH GdJi CSgd HGdLOI hGdSgh Je GdYbhd ai EUdGM GdCOhjI GdeSgdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs